Processing of nanostructures and their voltage-time characteristics / Noraini Abdul Rahman @ Hashim - Abdul Rahman @ Hashim, Noraini (2013)
The LiCo0.55Ni0.4Fe0.05O2 was prepared as nanostructure cathode materials using a high-energy ball milling method with different parameters. The nanostructure cathode materials was milling for 3 hours, 5 hours and< 10 hours. The nanostructure cathode materials prepared by high-energy ball milling method exhibit much smaller particle size than the non-ball milled cathode materials. The voltage-time curves for first cycle of nanostructure cathode material prepared by ball-milled was improved. The voltage-time was tested by using the Wonatech Electrical Tester. The 1mA was use to charging up to 4.3 V and 1Ma discharge up to 2.5 V. We tested the particle size by using SEM. The particle size was different for every parameter. The particle size of nanostructure cathode material ball-milled at 10 hour was smaller compared to non-ball milled nanostructure cathode material.